The feasibility of granulating and briquetting animal feed and poultry feed - Комар, Артем Станіславович; Komar, Artem (Запоріжжя : 2024, 2024)
UA: Modern conditions for the formation of economic relations in the agro-industrial complex provide for the development and introduction into production of small-sized energy-saving mechanization equipment with high operational reliability [1]. Existing means of mechanization, which increase the productivity of the process of creating complete feed and reduce its energy intensity, have a large mass and provide specific energy intensity. The use of such units in small farms leads to unreasonable energy consumption, which increases the cost of feed materials [2]. Bulk feed has disadvantages that reduce the efficiency of its use: low density, hygroscopicity and self-sorting of feed during transportation. The above disadvantages are largely eliminated by granulation and briquetting of mixed feed. The size of the granules depends on the type and age of animals and birds. For example, the diameter of pellets for young poultry should be no more than 3 mm, for adult poultry in the range of 4-5 mm, for weaned piglets - 5-8 mm, for adult pigs - 8-10 mm. The ratio of pellet length to diameter should not exceed 1.5 for poultry and 2 for animals.
Keywords: press installations; developing a design and technological scheme; granulated feed